2016
DOI: 10.1111/iej.12631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of apical periodontitis and root filled teeth in a Belgian subpopulation found on CBCT images

Abstract: The prevalence of AP was comparable with findings in other epidemiological studies. Root filled teeth had significantly more AP than nonroot filled teeth. The technical quality of the root fillings had a significant impact on the presence of AP. Therefore, emphasis on the quality of work and continuing education in the field of Endodontology must be provided in Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
5
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 55 publications
(214 reference statements)
4
50
5
5
Order By: Relevance
“…Additional important prognostic factors for tooth retention include the following: age (Imura et al , Landys Borén et al ), tooth type (Imura et al , Ng et al ), presence of mesial/distal contacts (Ng et al ) and post‐treatment type of coronal restoration (Ng et al , Landys Borén et al ). Several studies from different research groups unanimously highlight the high prevalence of periapical periodontitis associated with poor‐quality root fillings (Boucher et al , Segura‐Egea et al , Georgopoulou et al , Kabak & Abbott , Chala et al , Paes da Silva Ramos Fernandes et al , Dutta et al , Van der Veken et al , Huumonen et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional important prognostic factors for tooth retention include the following: age (Imura et al , Landys Borén et al ), tooth type (Imura et al , Ng et al ), presence of mesial/distal contacts (Ng et al ) and post‐treatment type of coronal restoration (Ng et al , Landys Borén et al ). Several studies from different research groups unanimously highlight the high prevalence of periapical periodontitis associated with poor‐quality root fillings (Boucher et al , Segura‐Egea et al , Georgopoulou et al , Kabak & Abbott , Chala et al , Paes da Silva Ramos Fernandes et al , Dutta et al , Van der Veken et al , Huumonen et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Contamination of the root canal system may arise in teeth with or without previous root canal treatment (Van der Veken et al 2016). However, several authors (Saunders et al 1997, De Moor et al 2000, L opez-L opez et al 2012 have reported that apical periodontitis is more prevalent in root filled teeth.…”
Section: Introductionmentioning
confidence: 99%
“…, Van der Veken et al . ), (ii) the numerous advantages of VPT in terms of preserving tooth structure (Reeh et al . ), maintaining possible proprioceptive defensive mechanisms of the remaining pulp, and reducing the propensity of tooth fracture (Randow & Glantz , Ou et al .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing number of investigations from Europe and other parts of the world indicate that AP is a remarkably prevalent disease among adults (Moreno et al, ; Sidaravicius, Aleksejuniene, & Eriksen, ; Van der Veken, Curvers, Fieuws, & Lambrechts, ; Vengerfeldt, Mändar, Nguyen, Saukas, & Saag, ). Frequency of AP varies between populations depending on diversity in caries prevalence, accessibility to dental care and methodological issues such as sampling and measurement differences.…”
Section: Introductionmentioning
confidence: 99%